(untitled) (International Journal of Scientific Trends, 2024)
This article analyzes the issues of efficient use of hard-to-recover oil fields by refining the geological and hydrodynamic model. As a result of refining the geological model and hydrodynamic studies, the efficiency of mining technologies is increased. This approach allows for resource conservation, optimization of production processes, and ensuring the environmental safety of the oil industry.